2016
DOI: 10.1093/mmy/myw069
|View full text |Cite
|
Sign up to set email alerts
|

Candidaspecies diversity and antifungal susceptibility patterns in oral samples of HIV/AIDS patients in Baja California, Mexico

Abstract: Candidiasis is the most common opportunistic fungal infection in HIV patients. The aims of this study were to identify the prevalence of carriers of Candida, Candida species diversity, and in vitro susceptibility to antifungal drugs. In 297 HIV/AIDS patients in Baja California, Mexico, Candida strains were identified by molecular methods (PCR-RFLP) from isolates of oral rinses of patients in Tijuana, Mexicali, and Ensenada. 56.3% of patients were colonized or infected with Candida. In Tijuana, there was a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
3
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 60 publications
6
16
3
11
Order By: Relevance
“…Consequently, increase resistance to the drug poses a threat not only to the treatment of oral candidiasis HIV/AIDS patient, but also to the management of systemic fungi infections HIV/AIDS patients. The other azoles recorded resistance which was closely similar to fluconazole; this is in contrary to previous study [ 28 ]. This is probably due to cross resistance to fluconazole, since all azoles exert the same mechanism of action and fluconazole was routinely administered to HIV/AIDS patients with clinical symptoms of candidiasis without prior antifungal susceptibility testing in these center.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Consequently, increase resistance to the drug poses a threat not only to the treatment of oral candidiasis HIV/AIDS patient, but also to the management of systemic fungi infections HIV/AIDS patients. The other azoles recorded resistance which was closely similar to fluconazole; this is in contrary to previous study [ 28 ]. This is probably due to cross resistance to fluconazole, since all azoles exert the same mechanism of action and fluconazole was routinely administered to HIV/AIDS patients with clinical symptoms of candidiasis without prior antifungal susceptibility testing in these center.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding indicated that amongst all Candida isolates tested, nystatin was the most sensitive antifungal drug (83.6%), followed by amphotericin (76%) and miconazole (74.3%). This finding partly agree with a similar study carried out in Mexico [ 28 ], where nystatin and amphotericin were the most sensitive antifungal tested. This finding is in contrast with a similar study carried out in Cameroon by Njunda et al [ 15 ], where ketonazole was found to be the most sensitive antifungal drug (85.5%).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this sense, it was recently demonstrated a higher prevalence of Candida species in the oral cavity of diabetic patients compared to non‐diabetics, being Candida albicans the most frequently isolated microorganism from the two groups of patients . This species was also the most found in the oral cavity of individuals carrying the human immunodeficiency virus …”
Section: Introductionmentioning
confidence: 96%